2001
DOI: 10.1034/j.1399-0012.2001.150201.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytological monitoring of peripheral blood, bronchoalveolar lavage fluid, and transbronchial biopsy specimens during acute rejection and cytomegalovirus infection in lung and heart–lung allograft recipients

Abstract: TBB histology remains the 'gold standard' for diagnosing rejection in lung and heart-lung transplantation patients, as the inflammatory cell findings in TBB specimens are highly specific for rejection. The cellular changes associated with rejection, mild PB basophilia and increased proportions of lymphocytes in early- and neutrophils in later-occurring rejection, observed in BAL-F cannot be considered specific for rejection, but may warrant clinical suspicion of rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…IL-17 correlated with the severity of AR. In agreement with data from other authors, the present authors also found an increase in BAL lymphocytes [4,12] and neutrophils [8] in AR. This increase in BAL lymphocytes and neutrophils, in patients with an AR episode at day 28, did not normalise when analysed at a 2-month follow-up examination.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…IL-17 correlated with the severity of AR. In agreement with data from other authors, the present authors also found an increase in BAL lymphocytes [4,12] and neutrophils [8] in AR. This increase in BAL lymphocytes and neutrophils, in patients with an AR episode at day 28, did not normalise when analysed at a 2-month follow-up examination.…”
Section: Discussionsupporting
confidence: 83%
“…The current authors also found BAL neutrophils to be increased and to correlate with the grade of AR. This increase was also demonstrated in several other studies, although not consistently [8,17,18]. These papers clearly illustrate that neutrophils may be present in BAL during AR.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations